Efeitos de parâmetros de extrusão nas propriedades físicas de produtos expandidos de inhame - Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP]; De Pinho, Sheila Zambello; Iatauro, Ricardo António [UNESP]; Duarte Filho, Jaime (FapUNIFESP (SciELO), 2006)
Effect of extrusion parameters was studied on the expansion index, specific volume, water absorption index (WAI) and water solubility index (WSI) of expanded yam snacks. The central composite design was used to study the parameters effect. It was verified three levels of temperature in the barrel (100, 115 and 130°C), three levels of screw speed (163, 204 and 245 rpm) and three levels of flour moisture (12, 15 and 18%). The results showed that expansion properties (expansion index and specific volume) depend on flour moisture and extrusion temperature. The WSI was dependant of three parameters. Higher levels of temperature and screw speed increase the water solubility index (WSI). The studied parameters did not influence the water absorption index (WAI).
Effect of extrusion parameters in the physical properties of expanded yam snacks
Keywords: Dioscorea alata; Expansion; Flour; Starch